Emphasizing rarity - laparoscopic management of an adrenal schwannoma: a case report and review of the literature - R., Shashank N.; Aggarwal, Lalit; Rastogi, Sukriti; Saroj, Pooja; Singh, Lakshya (International Surgery Journal, 2026)
Schwannomas are benign tumors arising from Schwann cells of peripheral nerve sheaths and are most commonly encountered in the head, neck, and extremities. Adrenal schwannomas originate from Schwann cells innervating the adrenal medulla and are typically non-functional, asymptomatic lesions discovered incidentally during imaging performed for unrelated reasons. Adrenal schwannoma is an exceptionally rare entity, accounting for less than 0.2% of all adrenal neoplasms, with fewer than 60 cases reported in the literature. Due to their rarity and nonspecific radiological appearance, these tumors are frequently misdiagnosed preoperatively as adenomas, pheochromocytomas, or adrenocortical carcinoma. We present a case of a non-functional adrenal schwannoma in a 55-year-old female, highlighting the diagnostic challenges and emphasizing the importance of histopathological confirmation.